Nuclear Power Decision-Making in New Brunswick, 1971-1975 - Secord, Andrew G. (Acadiensis, 2020)
This article explores the origins of the Point Lepreau nuclear reactor in southern New Brunswick, with a focus on the corporate strategies of the two state enterprises most directly involved: the New Brunswick Electric Power Commission (NBEPC) and Atomic Energy of Canada Limited (AECL). Although their nuclear decision was increasingly challenged from within the federal state, NBEPC officials worked aggressively to maintain their nuclear timeline and took on additional risks in the process. At the final decision point in 1974, they proceeded notwithstanding unforeseen increases in estimated construction costs and without potential partners.